Together : the science of social psychology - Biswas-Diener, Robert; Diener, Ed; BC Open Textbook Project; BCcampus (DEF Publishers, Noba Project, 2016)
"The science of social psychology investigates the ways other people affect our thoughts, feelings, and behaviors. It is an exciting field of study because it is so familiar and relevant to our day-to-day lives. Social psychologists study a wide range of topics that can roughly be grouped into 5 categories: attraction, attitudes, peace & conflict, social influence, and social cognition. This textbook presents core concepts common to introductory social psychology courses. The 8 units include 27 modules covering key social psych topics such as research methods, group processes, social influence, and relationships"--BC Campus website.
Social Psychology as a Science -- Understanding the Self and Others -- Groups and Group Processes -- Emotions -- Positive Relationships -- Industrial/Organizational Psychology.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references and index.
Mode of access: World Wide Web.
Online version. 2016; title from PDF (viewed on October 31, 2016).
Keywords: Psychology; Social psychology; Electronic books